LONG-TERM EXPOSURE TO MALARIA AND DEVELOPMENT: DISAGGREGATE EVIDENCE FOR CONTEMPORANEOUS AFRICA. (13th February 2017) - Cervellati, Matteo; Esposito, Elena; Sunde, Uwe
Abstract: Malaria afflicts mankind since thousands of years and still imposes serious health impediments and considerable mortality on the affected populations. Empirical investigations of the role of malaria for economic development at the country level deliver mixed findings, however. We study the role of long-term malaria exposure on development today using disaggregate within-country variation for the whole of Africa with 1 × 1 degree cells as units of observation. Local development is measured by light density at night. Based on insights from epidemiology, which documents that genetic and acquired immunities reduce Malaria risk for adults in holoendemic areas, the effect is hypothesized to be nonlinear, with a peak for intermediate rather than high exposure to the pathogen. The empirical findings support this hypothesis. The results also suggest the existence of a significant moderating effect of genetic immunities measured by the prevalence of the sickle cell trait in the population.